Thermal rearrangement of ortho-allyloxypolyimide membranes and the effect of the degree of functionalization. Issue 29 (7th June 2018) - Meis, David; Tena, Alberto; Neumann, Silvio; Georgopanos, Prokopios; Emmler, Thomas; Shishatskiy, Sergey; Rangou, Sofia; Filiz, Volkan; Abetz, Volker
Abstract : Aromatic polyimides containing different ratios of ortho -hydroxy to ortho -allyloxy units were prepared and thermally rearranged. Abstract : Aromatic polyimides containing an ortho -allyloxy group with different ratios (in the range of 10–100%) of the ortho -allyloxy to ortho -hydroxy units were synthesized. The allyl ether synthesis was done via a post-polymerization Williamson etherification reaction. Thermally induced Claisen-rearrangement of the allyloxy-phenyl unit was conducted in the solid-state, followed by isothermal treatments at 250 °C leading to a crosslinked ortho -hydroxy containing polyimide. Further thermal annealing at 350 °C was employed to achieve a high imide-to-benzoxazole conversion, commonly described as the thermal rearrangement process (TR). The influence of the degree of modification on the crosslinking reaction as well as the imide-to-benzoxazole conversion temperature and the rate were studied by means of TG-FTIR, DSC and dielectric spectroscopy. A nearly linear change of the material properties, such as film density, d -spacing and gel-fraction, with an increasing number of allylated units was observed. Additionally, an incline of the permeability, due to an increase of the free volume elements, was observed. Moreover, the polymer chain mobility in terms of relaxation times was demonstrated to depend on the degree of allylation, which in turn led to a reduction of the TR temperature of about 80 °C compared to the pristine polyimide. The thermally induced imide-to-benzoxazole rearrangement occurred already to a large extent of 77% at 350 °C. In comparison, the pristine polymer showed only a conversion of 20%. Furthermore, the observed HPI-to-PBO conversions at 350 °C surpassed those of various other reported TR polyimides treated at even higher temperatures of 400 to 450 °C. Side-reactions and degradation that usually accompany treatments at 400 °C and above might be avoided at lower treatment temperatures of 350 °C.